Freedom as an educational practice in order to transform a classroom plains. (2014)
Education notes challenging training committed to strengthening human qualities versus expectations ofevery being and social needs. This commitment is reflected in the actions and practices that are assumedas an opportunity to enhance the capabilities of human beings. From this inspiration comes the need totransform educational practice in a first grade classroom in the city Villavicencio, where commitments,goals and actions are articulated to build experiences freedom from school every day.